Ketahanan pangan sebagai deteminan kejadian stunting pada anak usia 2-3 tahun di Kabupaten Ciamis-Jawa Barat - Betaditya, Dika; Julia, Madarina; Nisa, Fatma Zuhrotun (Jurnal Gizi Klinik Indonesia, 2022)
Determinant of stunting in children 2-3 aged years in Ciamis District West Java ProvinceBackground: The prevalence of stunting in Indonesia is still high (at 37,2%), while in the province of West Java is at 35,8%. Household food security is one of the indirect causes of the nutritional problems. Aspects of food security in the form of food availability and access to food are related in a household that affects the aspect of the level of food consumption in every household or individual that is not being met. Objective: The study aims to analyze whether household food security was the determinant of stunting in children aged 2-3 years in Ciamis Districts. Methods: This was an observational study with a case-control design. Subjects in this research are households. Information from a total of 349 households, i.e. 168 had stunted and 181 without stunted children, were collected. Respondents consisted of mothers, fathers, and children aged 2-3 years in Ciamis District. Subjects were selected using quota sampling. Data were analyzed using t-test and logistic regression. Results: Food availability, food access, energy, and protein consumption were not associated with stunting (p>0,05). There were significant differences between the average height (Z-score) of children based on the father's height, the mother's height, and the mother's education level (p<0,05). Breastfeeding, initial formula feeding, father's education level, and a large number of families were not associated with stunting (p> 0,05). Conclusion: This study observed that household food security was not the determinant of stunting. After controlling for potential confounders, the children's heights were independently associated with parental heights and maternal education.